Gender Gaps in Albania through the Lens of Poverty and Shared Prosperity : Findings from the 2012 LSMS - Golla, Anne Marie; Dávalos, María E. (World Bank, Washington, DC, 2016)
This report analyzes gender dimensions of poverty and shared prosperity in Albania using data from the most recent rounds of the Living Standards Measurement Survey (LSMS) Albania. The goal is understand both the distribution of poverty and lower economic outcomes for women and the underlying gender gaps contributing to these disparities. Two frameworks are used: the ECA Region Shared Prosperity Framework, which analyzes how productive assets create prosperity at the household level, and the World Development Report on Gender and Development, which presents an explicitly gendered framework in which individuals, households, and institutions interact.3 The report considers household composition, education, labor force participation and outcomes, social transfers, social capital, access to technology, and subjective poverty. The period available in the data, from 2008 to 2012, corresponds to the global financial crisis, which had a severe impact on the Albanian economy. This provides the opportunity to examine how key outcomes for women changed in a period of economic downturn. The report provides a rapid, broad overview of gender gaps based on new data from the 2012 LSMS, in the context of the Shared Prosperity and WDR frameworks. It examines gender differences between who is poor and in the bottom 40 percent of the population, and how they have changed since 2008. To understand the causes of gendered differences in poverty, the report then looks at gaps in key assets, asset use, wages, and transfers between men and women in 2012, as well as whether these gaps have widened or narrowed since 2008. The report is not meant to provide a complete and updated gender diagnostic for Albania, which would require review of policies and institutions and how they impact women’s endowments, use of endowments, and ability to benefit from the returns to endowments. The 2012 data also do not provide a complete picture of gender in marginalized ethnic communities or specific rural areas, because the survey design did not oversample these groups. This report uses primarily the official definition of poverty as those in households with per-person consumption of less than the national poverty line (6,412new lek/month). However, the final sections on social capital and participation and subjective poverty address some additional components of poverty included in more comprehensive definitions, individual experiences with poverty, ability to participate in society, and ability to access basic needs.